Developing synthetic strategies and studying potential applications of buckybowl corannulene polymers - Zhang, Zhuang (Nanyang Technological University, 2020)
The bowl-shaped polycyclic aromatic (C20H10) hydrocarbon, corannulene, constitutes a recognizable motif on the curved surface of buckminsterfullerene (C60). Therefore, the scientific community has heavily investigated it for its structure and properties. One aspect that is still relatively less studied is its application in the arena of macromolecular science. In the past 50 years of corannulene chemistry, only a few synthetic examples are known in this context. Therefore, the aim of this thesis is to examine corannulene derivatives as polymerization initiators and monomers to access novel polymers and study their properties and applications. In this regard, the first chapter of this thesis introduces the reader with the literature so far on polymers of corannulene. In the second chapter synthesis of corannulene is described. In the third chapter, preparation of corannulene-based polymerization initiator is discussed and linear polymers are synthesized successfully using atom transfer free radical polymerization method. In the fourth chapter, corannulene is used as a monomer in palladium-catalyzed Stille polycondensation process to access network geometry. The morphology of these polymers was investigated and finally they were applied in supercapacitor devices. This work indicated that corannulene polymers are potential active materials for electrochemical energy storage and the devices show good stabilities and long recyclability. In essence, this thesis work enhances the repertoire of corannulene polymers and shows their applicability in real life devices.